Bacterial and Host Determinants of Group B Streptococcal Infection of the Neonate and Infant - Furuta, Anna; Brokaw, Alyssa; Manuel, Gygeria; Dacanay, Matthew; Marcell, Lauren; Seepersaud, Ravin; Rajagopal, Lakshmi; Adams Waldorf, Kristina (Frontiers in Microbiology, 2022)
Group B streptococci (GBS) are gram-positive beta-hemolytic bacteria that can cause serious and life-threatening infections in neonates manifesting as sepsis, pneumonia, meningitis, osteomyelitis and/or septic arthritis. Invasive GBS infections in neonates in the first week of life are referred to as early-onset disease (EOD) and thought to be acquired by the fetus by exposure to GBS in utero or to vaginal fluids during birth. Late-onset disease (LOD) refers to invasive GBS infections between 7 and 89 days of life. LOD transmission routes are incompletely understood, but may include breastmilk, nosocomial, or community sources. Invasive GBS infections and particularly, meningitis, may result in significant neurodevelopmental injury and long-term disability that persists into childhood and adulthood. Globally, EOD and LOD occur in more than 300,000 neonates and infants annually, resulting in 90,000 infant deaths and leaving more than 10,000 infants with a lifelong disability. In this review, we discuss the clinical impact of invasive GBS neonatal infections and then summarize virulence factors that allow the bacteria to exploit the developing neonatal immune system and target organs. Specifically, we consider the mechanisms known to enable GBS invasion into the neonatal lung, blood vessels and brain. Understanding mechanisms of GBS invasion and pathogenesis relevant to infections in the neonate and infant may inform the development of therapeutics to prevent or mitigate injury.